Virulent and attenuated strains of Trichoderma citrinoviride mediated resistance and biological control mechanism in tomato - Zhao, Di; Shen, Dan; Fan, Haiyan; Zhu, Xiaofeng; Wang, Yuanyuan; Duan, Yuxi; Chen, Lijie (Frontiers in Plant Science, 2023)
Root-knot nematode disease is one of the world's most serious vegetable crop diseases. In recent years, Trichoderma spp. has been widely used in root-knot nematode disease control as a biological control agent. Preliminary experiments found differences in nematicidal virulence among Trichoderma citrinoviride. The 24-hour corrected mortality rate of the virulent strain T1910 was as high as 92.37%, with an LC50 of 0.5585 against the second juveniles (J2s) of Meloidogyne incognita. And the attenuated strain TC9 was 23.01%, the LC50 was 2.0615, so the virulent strain T1910 had a more substantial effect on the J2s than the attenuated strain. We found that the strong virulent strain T1910 have a good control effect on M. incognita by the pot experiment of tomato than that of the attenuated virulent strain TC9, especially the J2 and J4 numbers were inhibited inside the root knots of tomato. To reveal the differences in tomato defense pathways induced by different virulent strains, qRT-PCR was further used to detect changes in the expression of inducement-related genes. The results showed that the TC9 was significantly upregulated at 5dpi, LOX1, PR1, and PDF1.2. The PR5 gene of the virulent strain T1910 was highly upregulated, and the JA pathway was activated later but weaker than the attenuated strain. The results of this study revealed that the biocontrol mechanism of T. citrinoviride was poison killing through the virulent strain T1910 and induced resistance to M. incognita through attenuated strain, although virulence degradation also has an induced resistance effect. Moreover, the attenuated strain TC9 stimulated tomato immune response earlier than the virulent strain by NAMP. Therefore, the research elucidated the mechanism of multiple control of Trichoderma spp. against M. incognita.